The Assessing of Inappropriate Admissions and Hospitalization based on Appropriate Evaluation Protocol in Alinasab hospital in Tabriz- 2009 - J Fekari; A ghiasi; M Ezzati; M Pakdaman; A Khalafi (Tehran University of Medical Sciences, 2011)
Background: Assessing applied resources in a hospital as a health system will lead to identify organizational problems in this section and subsequently the necessary actions to resolve them. The aim of this study was to determine measurement of inappropriate admission and hospitalization (ISP: Inappropriateness Patient Stay) and associated reasons. Materials & Methods: One widely used tools to assess appropriate use of hospital recourse is Appropriateness Evaluation Protocol which include objective criteria related to clinical services provided to the patient. Survey of admission and hospitalization in a cross-sectional and prospective study for 246 patients in the Alinasab hospital affiliated insurance organization carried out in Tabriz. Results: The total of 7 percent of admissions and 6.2 percent of hospitalized were diagnosed inappropriate manner. There was no significant association between inappropriate admissions and other variables. There was significant relationships between Inappropriate bed days with insurance (P=0/041) and duration of hospital stay (P=0/041). However, there were no association between sex, disease diagnosis and hospital days per week with Inappropriate bed days. Conclusion: The reasons of inappropriate admission and hospitalization in Iran are similar to other countries. Upgrading strategies to referral system performance, creating standard protocols to evaluate criteria for medical personnel and increasing outpatient diagnostic institutions could be reduce inappropriate admissions and stay of patients.